Complexity & Development 2.0: From Agreeing We Should Adapt to Creating the Conditions that Enable Adaptation - and Ang, Yuen Yuen (2018)
The field of global development has reached a critical turning point. Almost gone is the mechanical, one-size-fits-all “good governance” paradigm of the past. In its place is a growing embrace of complexity and systems thinking. While this is an encouraging shift in the right direction, the discussion mostly ends by concluding that we should adapt. Yuen Yuen Ang urges that it’s time to take our conversation on “complexity & development” to the next level: how to enable adaptation. Effective adaptation doesn’t automatically arise just because we desire it—rather, it requires certain enabling conditions. In How China Escaped the Poverty Trap (2016), she introduces a generic complexity 2.0 framework that she terms “directed improvisation.” Effective adaptation, Yuen Yuen argues, requires a paradoxical blend of top-down direction and bottom-up improvisation. Such a system can be created—and produce dramatic results and adaptive solutions—even within a closed political regime like China.